Hermeneutika Hadis: Tinjauan Pemikiran Yusuf Al-Qordhowi Dalam Memahami Hadis - Fahimah, Siti (MADINAH, 2017)
Hadis as the Qur'an is a text produced from the past and destined for all time, past and present. In understanding the products of the past many methods for its understanding can be catered for the benefit of the people. Hermeneutics is present as a new method for understanding past product texts in order to be applied to the present, in the heremenutics are three kinds, those are texts, contexts and authors can unite to produce a 'similar' understanding to what the text writer intended Allah (al-Qur'an) or Prophet Muhammad (Hadith). In understanding the text of the Qur'an has been offered an understanding by using methods of heremeneutic with clear steps, as well as Hadith, many ways of understanding hadith, among which was put forward by Yusuf Qordhowi, he emphasized the understanding of hadith on maqashid as-syariah and pay attention to asbab al-wurud hadith and try to find its contextual significance. In an attempt to understand the hadith, Al-Qordhowi mindset has been constructed in such a way that he in understanding the hadith always concerns the internal of the hadith without forgetting to use the external approach. Where the intersection between the goal of understanding hermeneutics with the study of Yusuf Qordhowi’s Hadis.